The gastric carcinosarcoma with severe venous invasion: a case report - Tomoaki Bekki (Surgical Case Reports, 2018)
Abstract Background Gastric carcinosarcoma with severe venous invasion is extremely rare, and to the best of our knowledge, this is the first reported case. Case presentation A 79-year-old man visited the Onomichi General Hospital following abnormal upper gastrointestinal series findings. Laboratory data demonstrated no anemia, and the serum carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) levels were not elevated. Endoscopy identified a Borrmann type III lesion in the cardiac end of the stomach. Abdominal contrast-enhanced computerized tomography (CT) indicated that the lesser curvature of the stomach wall was modestly enhanced with bulky lymph nodes. Pathological biopsy examination identified a group 5, papillary adenocarcinoma. We diagnosed advanced gastric cancer with bulky lymph nodes (cT4aN3M0, cStage IIIC). Following neoadjuvant chemotherapy, the patient underwent open total gastrectomy with D2 lymph node dissection. Histopathologically, the tumor consisted of two components: a tubular adenocarcinoma and a sarcoma. The tumor cells were mainly intravenous and were not detected in the gastric wall stroma; this resulted in a venous invasion. Immunohistochemical analysis revealed that the tumor was positive for vimentin and partly positive for desmin and cytokeratin CAM5.2. We diagnosed a true gastric carcinosarcoma with severe venous invasion. Abdominal CT 2 months after surgery showed a low density area in the liver, suggesting metastasis. Conclusions Carcinosarcomas with lymph node metastasis are sometimes reported, but progression into the vasculature is very rare. We present a case of carcinosarcoma with unusual progression characteristics.